Pelatihan Public Speaking dan Pengkabelan Jaringan Komputer sebagai Upaya Peningkatan Kompetensi Siswa SMP YPK Sele be Solu - Melda Agnes Manuhutu; Donal Donal; Agustina Agustina; Boyke Boyke; Elshaday Elshaday; Julia Julia; Julian Julian; Margaretha Margaretha; Darma Darma; Mariam Mariam; Sherly Gaspersz; Lulu Jola Uktolseja (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2026)
The Public Speaking and Computer Network Cabling Training Activity at SMP YPK Sele Be Solu aims to improve students' competence in communication and technical skills in computer networking. The activity was carried out using an experiential learning approach with stages of observation, socialisation, hands-on training, and evaluation. The results of the activities show an increase in students' confidence in public speaking and basic technical skills in network cabling, including LAN cable installation, RJ-45 connectors, and cable testing. Intensive mentoring during the training helped students overcome difficulties and optimise their understanding. This activity demonstrates that combining soft skills and hard skills training through direct experience can improve students' overall competence, motivate learning, and prepare students to face academic and digital challenges in the future. In addition, this activity also strengthened cooperation between schools and universities in supporting the improvement of skills-based education quality. The enthusiasm of students during the training showed that practice-based learning methods are very effective at the junior high school level. With this activity, students have a strong foundation to develop their interests and potential in the fields of communication, information technology, and readiness to face the rapidly developing digital world.